Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) Terhadap Hasil Belajar Pendidikan Kewarganegaraan (PKn) Siswa Kelas V SDN 199 Arasoe Kecamatan Cina Kabupaten Bone - A Rahim; Auliah Andika Rukman (JED (Jurnal Etika Demokrasi), 2017)
This type of research is pre-experimental research of One-Group Preview-Posttest Design that is an experiment which in its implementation only involves one class as experiment class without any class of control class which aims to know the influence of STAD type cooperative learning model toward student learning result of Civics class V SD Negeri 199 Arasoe District of China Bone Regency of academic year 2015/2016. The experimental unit in this study is a Class V student of 20 people. The study was conducted for 6 meetings. Student learning outcomes using STAD type cooperative learning model show better learning outcomes than before the learning model was applied. The result of inferential statistic analysis using t test formula, it is known that t value obtained is 8.8 with frequency db = 20-1 = 19, at 5% significance level obtained t Table = 2.09. So, t Count t table. This proves that there is influence of STAD type of cooperative learning model (Student Team Achievement Division) to the learning outcomes of Citizenship Education (Civics) of Grade V of SD Negeri 199 Arasoe Sub-District of Bone District of China.Keywords: Pre-experimental, STAD Type Co-operative Learning Model